Theory and Practice of Translation in Pedagogical Activities (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article focuses on translation practice that helps students acquire, develop, and strengthen their knowledge and skills in a foreign language. Translation integrated into the practice of language learning along with generally accepted learning activities such as reading, listening, writing and vocabulary development can be described as a “pedagogical tool” as its purpose is language learning. Translation activity forces students to communicate in two directions: from a foreign language and into it. During translation, students are encouraged to notice differences in structure and vocabulary, strengthen grammatical skills, shape their own way of thinking, and correct common mistakes that might otherwise go unnoticed. Students can get the most out of their learning if they are encouraged to use their translation skills correctly. Translation is a good tool for learning a foreign language.